Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/atmos13081285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Urban Road Green Belts on Pedestrian-Level Wind in Height-Asymmetric Street Canyons

Abstract: This study was conducted to examine the effect on airflow of the shape of an urban road green belt in an asymmetrical street canyon. In this paper, the airflow field at pedestrian height in an asymmetrical street with different building height ratios (ASF) on both sides of the street is modeled and simulated using computational fluid dynamics (CFD) software, ANSYS FLUENT, and the flow rate characteristic distribution index and the average airflow intensity index are used to evaluate and analyze the airflow at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…By 2018, this proportion had surged to 55%. Projections indicate that this trend of urbanization will continue, with urban populations reaching an estimated 66% of the global population by the year 2050 [1]. China has notably exemplified this trend, undergoing a transformative surge in urbanization from 17.92% in 1978 to 52.27% in 2012, primarily attributed to the transformative policies of Reform and Opening [2].…”
Section: Introductionmentioning
confidence: 99%
“…By 2018, this proportion had surged to 55%. Projections indicate that this trend of urbanization will continue, with urban populations reaching an estimated 66% of the global population by the year 2050 [1]. China has notably exemplified this trend, undergoing a transformative surge in urbanization from 17.92% in 1978 to 52.27% in 2012, primarily attributed to the transformative policies of Reform and Opening [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that vegetation, especially trees in urban areas, has a favorable effect on the local wind environment [8,9]. On the one hand, trees reduce the wind speed behind them in urban areas by hindering the high-speed flow of incoming wind [10], changing the fluidity of the adjacent areas near the ground [11] and improving the comfort and health of the wind environment.…”
Section: Introductionmentioning
confidence: 99%